Bioassay Guided Fractionation of Ciplukan (Physalis angulata L.) Monitored by Glucose Consumption Assay and Thin Layer Chromatography on Myoblast Cells - Mae Sri Hartati Wahyuningsih; Ketut Shri Satya Wiwekananda; Aurelia Priscilla Regita Putri; Dwi Aris Agung Nugrahaningsih; Mia Munawaroh Yuniyanti (Majalah Obat Tradisional, 2023)
Ciplukan (Physalis angulata Linn.) has been used by the community as an anti-diabetic drug. The antidiabetic effect is due to ingredients such as unsaturated fatty acids, alkaloids, flavonoids, saponins, polyphenols, steroids, triterpenoids, monoterpenoids, and sesquiterpenoids. Part of the fruit of P. angulata contains many active substances of flavonoids with the proportion of fruit extract 300 μg/ml is 84%. Therefore the exploration for compounds responsible for antidiabetic activity in P. angulata needs to be done to ensure empirical evidence. The purpose of this study was to find the active fraction of P. angulata L. which has anti-hyperglycemic properties. This study used Myoblast cells as subjects and the Bioassay Guided Fractionation method for separating compound groups through three stages of the extraction, partitioning, and fractionation processes which were monitored using TLC and the Glucose Consumption Assay test. The results showed that the chloroform extract (CHCl3) was more active in lowering glucose levels compared to the methanol extract (MeOH) (4.86% vs -8.74%). MeOH insoluble extract was more active than MeOH soluble extract (5.14% vs -8.52). The fractionation results showed that Fraction I was the most active in lowering glucose levels compared to FII, III, and IV (26.47%; 13.18%; 0.15%; 13.76%). Therefore Fraction 1 which contains a class of flavonoid compounds is a potential candidate to be developed as an antidiabetic agent.